Comparison of The Effectiveness of Grape Seed (Vitis Vinifera) With Aloe Vera (Aloe Vera) in The Repair of Burns in Wistar Rats Based on Wound Diameter - Yashinta Maria Veronica; Oliviti Natali; Djohan Djohan (Eduvest - Journal of Universal Studies, 2024)
Burns are tissue damage or loss caused by contact with heat sources such as fire, hot water, chemicals, electricity and radiation. The grape plant has an activity of pharmacological effects, which are mainly present in its seeds and fruits. Grape seed extract containing proanthocyanidin can help wound healing by promoting neovascularization, extracellular matrix remodeling, fibrolastic cell migration and differentiation. Aloe vera leaves can be used to treat skin lesions, such as burns, irradiation damage and ischemic ulcers. In addition to being a hydrating and skin- protecting agent, this gel also has healing, analgesic, and anti-inflammatory activities because aloe vera contains vitamins C and E, essential amino acids, and polysaccharides that stimulate tissue growth and cell regeneration. The objective is to determine the effectivity of burn wound repair using grape seed extract and aloe vera. This research used 24 white rats weighing 150 to 200g that divided into 4 groups, positive control group, negative control group, 10% grape seed extract treatment group, and 10% aloe vera extract treatment group. This study used an experimental method with True Experimental design with Randomized Post-test only Control Group Design, by giving 10% concentration of grape seed extract and aloe vera extract with 10% concentration to rats that has been burnt.